Energy and exergy analyses of drying of apricots in a rotary solar dryer - Akpinar, E. Kavak; Sarsilmaz, C. (My University, 2004)
This paper presents the energy and exergy analyses of the drying process of apricots in a rotary column cylindrical drying (RCCD) cabinet. For these purposes, all stages of the drying process, considered as a steady-flow thermodynamic system, were analysed. Using the first law of thermodynamics, energy analysis was carried out to estimate the amounts of energy gained from solar air collectors and the ratios of energy utilisation. However, exergy analysis was accomplished to determine the type and magnitude of exergy losses during the solar drying process by applying the second law of thermodynamics. It was observed that the apricot samples sufficiently dried in the range 38–57.8°C drying air temperature and 20.5–49.7% relative humidity, at 2.3 ms-1 of drying air velocity and 2.25 rpm rotary speed of column in 76 h despite exergy losses of 0.1370–0.5612 kJkg-1. © 2004 Inderscience Enterprises Ltd.
Keywords: apricot; energy and exergy analyses; solar drying